Groundwater arsenic in Bangladesh: what's new for policy research? - Balasubramanya, Soumya; Horbulyk, Theodore M. (IWA Publishing, 2018)
This paper provides an overview of policy responses to arsenic in groundwater in rural Bangladesh to assess their role and potential effectiveness in reducing exposure. With 97% of the country consuming groundwater for drinking, there is a continuing crisis of tens of millions of people exposed to elevated levels of arsenic. An examination of the number of people protected through two major remediation efforts suggests that recent progress may not be sufficient to keep up with the increasing population or to resolve the crisis during this century. Recent developments in remedial options are examined to identify their potential role in an evolving policy and research agenda. There appears to be growing agreement about future research and policy responses that can scale remedial options and make them widely accessible. These include: (1) the need for a reliable and affordable programme of arsenic testing and retesting; (2) attention to risks from other soluble contaminants and pathogens; (3) explicit priority setting across locations, time and to address fairness; and (4) development of value chains to ensure remedial options are supported over time.